Virtual Try-on Experience Mobile Application with Augmented Technology for Jewelry Business - Kielarova, Somlak Wannarumon; Riyamongkol, Panomkhawn; Waranusast, Rattapoom; Tamwattanakul, Piyarach; Sirikamnoi, Pongsakorn; Sansri, Sunisa (Naresuan University Engineering Journal, 2021)
This paper proposes the development of virtual try-on experience mobile application, by using augmented reality technology, for online jewelry customers virtually trying-on jewelry products to increase opportunity to sale products. The proposed system is developed using marker less technique. It applies the recognition technique to detect user’s hand. The three-dimensional (3D) model of the jewelry product with realistic rendering is modeled in which could be changed its details and size according to customer’s requirement. This method can reduce the production costs of the conventional process. The accuracy of the position of 3D ring model on finger is approximately 94.17% and 100% for the case of bangle. From testing with jewelry entrepreneurs and customers, the results reveal that the use of the proposed try-on experience mobile application in terms of ease-of-use and increasing confidence in making purchasing decisions are highest appreciated, while the realistic look issue is highly satisfied.